English for Medical Purposes: The Case of Korean Cosmetic Surgeons - Baba Khouya, Youssef (Journal of Natural Language and Linguistics, 2024)
EMP (English for medical purposes) has received more interest in South Korea to enhance the English competence of professionals working in medical contexts. Consequently, this study is based on two objectives: 1) to clarify cosmetic surgeons’ English needs and 2) to delve into cosmetic surgeons’ views regarding EMP courses they attended, focusing on the extent to which those courses met their English language needs. Data were gathered from 21 cosmetic surgeons through semi-structured interviews. The participants work at four hospitals in Seoul, which receive cosmetic surgery clients worldwide. The results conclude that most participants have to sharpen their communicative skills and strategies to establish effective doctor-client relationships and give outstanding health care. Nevertheless, the participants encountered English communication breakdowns because of the need for more productive vocabulary, unusual accents, and pronunciation issues. The cosmetic surgeons stated that the EMP courses they attended were not as helpful as expected, as the content did not match their English language needs at work. Therefore, the results imply that EMP courses’ teachers and designers have to create programs to meet the cosmetic surgeons’ English language needs.